Diagnosis and management of overactive bladder: A review. Issue 5 (16th February 2021) - Nitti, Victor W.; Patel, Anand; Karram, Mickey
Abstract: Aim: Overactive bladder (OAB) is a common and troublesome condition that can significantly impair quality of life. This review aims to educate providers of obstetrics and gynecology services about available therapies for OAB and what to expect following treatment. Methods: Here, we review published data from studies that have evaluated available treatments for OAB. Relevant articles published over the past 2 decades, including large multicenter trials, were identified through a literature search using PubMed.gov, and the references in those articles were also manually searched to find additional articles. Treatment guidelines and product labels were also reviewed. Results: Behavioral therapy is recommended as a first choice for OAB management; pharmacologic treatment (anticholinergics, β3 ‐adrenoceptor agonists) as second‐line treatment; and onabotulinumtoxinA, peripheral tibial nerve stimulation, and sacral nerve stimulation as third‐line therapy for patients refractory or intolerant to first‐ and second‐line treatments. A stepwise approach to treatment through first‐, second‐, and third‐line therapies is recommended, recognizing this may not be appropriate for all patients. Conclusions: To optimize symptom control and set realistic expectations, patients should be carefully monitored and counseled appropriately on available treatment options.